2015
DOI: 10.7717/peerj.846
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary observations on the mandibles of palaemonoid shrimp (Crustacea: Decapoda: Caridea: Palaemonoidea)

Abstract: The mandibles of caridean shrimps have been widely studied in the taxonomy and functional biology of the group. Within the Palaemonoidea the mandibles reach a high level of structural diversity reflecting the diverse lifestyles within the superfamily. However, the majority of studies have been restricted to light microscopy, with the ultrastructure at finer levels poorly known. This study investigates the mandible of nine species belonging to six of the recognised families of the Palaemonoidea using SEM and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Interestingly, based on similar stable isotope carbon measurements, Kennedy et al (2001) concluded that the commensal pinnotherid Pontonia pinnophylax (Otto, 1821) assimilated similar food to its bivalve host P. nobilis . Further, and based on the form of the mandibles in the palaemonoids examined by Ashelby et al (2015), six types appear to relate to an individual taxon's feeding mode and/or diet. Pontonia pinnophylax has Type A mandibles that are also typical of the largely carnivorous palaemonid Palaemon macrodactylus Rathbun, 1902.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, based on similar stable isotope carbon measurements, Kennedy et al (2001) concluded that the commensal pinnotherid Pontonia pinnophylax (Otto, 1821) assimilated similar food to its bivalve host P. nobilis . Further, and based on the form of the mandibles in the palaemonoids examined by Ashelby et al (2015), six types appear to relate to an individual taxon's feeding mode and/or diet. Pontonia pinnophylax has Type A mandibles that are also typical of the largely carnivorous palaemonid Palaemon macrodactylus Rathbun, 1902.…”
Section: Discussionmentioning
confidence: 99%
“…5A). In fact, even in Gnathophyllum elegans , the type species of the family Gnathophyllidae, a vestigial incisor is present (see Ashelby, De Grave & Johnson, 2015 , Fig. 5A).…”
Section: Discussionmentioning
confidence: 99%
“…This is congruent with the host choices of the species in most of the studied genera (supplementary appendix S1), but this does not explain the seemingly difficult switch from one phylum to another. One explanation for these seemingly unexpected host switching events can be found in the internal structures of the host phyla: the studied shrimp species living inside bivalve molluscs are reported as inhabitants of the mantle cavity (e.g., Fransen, 1994), feeding from the mucus and pseudofeces which are built up near the gills (e.g., Kennedy et al, 2001;Ashelby et al, 2015;De Grave et al, 2021). This soft, mucus-producing internal cavity might be morphologically similar to the pharyngeal basket of phlebobranch and stolidobranch solitary ascidians (Horká et al, 2016, for comparison, see Monniot, 1991.…”
Section: Host Switching and Notes On Ecomorphological Charactersmentioning
confidence: 99%